Extracellular Purine Metabolism Is the Switchboard of Immunosuppressive Macrophages and a Novel Target to Treat Diseases With Macrophage Imbalances - Ohradanova-Repic, Anna; Machacek, Christian; Charvet, Celine; Lager, Franck; Le Roux, Delphine; Platzer, René; Leksa, Vladimir; Mitulovic, Goran; Burkard, Thomas R.; Zlabinger, Gerhard J.; Fischer, Michael B.; Feuillet, Vincent; et al. (Frontiers in Immunology, 2018)
If misregulated, macrophage-T cell interactions can drive chronic inflammation thereby causing diseases, such as rheumatoid arthritis (RA). We report that in a proinflammatory environment, granulocyte-macrophage (GM-CSF)- and macrophage colony-stimulating factor (M-CSF)-dependent macrophages have dichotomous effects on T cell activity. While GM-CSF-dependent macrophages show a highly stimulatory activity typical for M1 macrophages, M-CSF-dependent macrophages, marked by folate receptor β (FRβ), adopt an immunosuppressive M2 phenotype. We find the latter to be caused by the purinergic pathway that directs release of extracellular ATP and its conversion to immunosuppressive adenosine by co-expressed CD39 and CD73. Since we observed a misbalance between immunosuppressive and immunostimulatory macrophages in human and murine arthritic joints, we devised a new strategy for RA treatment based on targeted delivery of a novel methotrexate formulation to the immunosuppressive FRβ+CD39+CD73+ macrophages, which boosts adenosine production and curtails the dominance of proinflammatory macrophages. In contrast to untargeted methotrexate, this approach leads to potent alleviation of inflammation in the murine arthritis model. In conclusion, we define the macrophage extracellular purine metabolism as a novel checkpoint in macrophage cell fate decision-making and an attractive target to control pathological macrophages in immune-mediated diseases.